2013
DOI: 10.1103/physrevlett.111.143401
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Ion Charge Distribution from Cluster Nanoplasmas

Abstract: In nearly all the intense laser experiments with nanoclusters, the key observation has been that immense ionization drives highly charged ions to highest energies while low charge ions, if any, have lower kinetic energies. We show experimental measurements that are contrary to this established notion. The active role of outer-ionized electrons in a multicluster interaction is shown to effectively reduce high charge ions to low charge states with no loss of momentum. The role of Rydberg excited clusters, intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The mean charge is shown to reduce from 7.6 to 2.8 where Ar 2+ becomes the most dominant with the same energy as that of the highly charged ions. Our ECTREC formalism has been shown to reproduce well the charge histograms that are experimentally measured by accounting for the charge state dependent charge transfer rates [33].…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The mean charge is shown to reduce from 7.6 to 2.8 where Ar 2+ becomes the most dominant with the same energy as that of the highly charged ions. Our ECTREC formalism has been shown to reproduce well the charge histograms that are experimentally measured by accounting for the charge state dependent charge transfer rates [33].…”
Section: Resultsmentioning
confidence: 65%
“…Ions are reduced to neutrals by the enhanced charge transfer from Rydberg excited clusters (ECTREC). The charge transfer physics has also been shown to comprehend well the charge reduction for the different charge states produced in these clusters [33]. In these experiments the ionization of isolated Ar clusters is shown to produce a wide charge distribution with Ar 8+ as the most dominant ion and a mean charge of 7.6.…”
Section: Resultsmentioning
confidence: 91%
“…It was found that while the ion energies change very little, the ion charge states, as observed in Thompson parabola spectrometry [17], are reduced to an anomalously low value [12]. The unusually large charge-transfer rate that occurs in the transit of the supersonic jet could not be explained by the normal charge-transfer reactions or the electron recombination processes.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, experiments carried out nearly at 100 times larger cluster densities, where the spatial extent of the cluster jet is also much larger than the laser focus, have revealed hitherto unanticipated intracluster dynamics [12][13][14][15][16]. It was found that while the ion energies change very little, the ion charge states, as observed in Thompson parabola spectrometry [17], are reduced to an anomalously low value [12].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation